Chemometrics comparison of gas chromatography with mass spectrometry and comprehensive two‐dimensional gas chromatography with time‐of‐flight mass spectrometry Daphnia magna metabolic profiles exposed to salinity. Issue 11 (30th March 2018) - Parastar, Hadi; Garreta‐Lara, Elba; Campos, Bruno; Barata, Carlos; Lacorte, Silvia; Tauler, Roma
Abstract: The performances of gas chromatography with mass spectrometry and of comprehensive two‐dimensional gas chromatography with time‐of‐flight mass spectrometry are examined through the comparison of Daphnia magna metabolic profiles. Gas chromatography with mass spectrometry and comprehensive two‐dimensional gas chromatography with mass spectrometry were used to compare the concentration changes of metabolites under saline conditions. In this regard, a chemometric strategy based on wavelet compression and multivariate curve resolution–alternating least squares is used to compare the performances of gas chromatography with mass spectrometry and comprehensive two‐dimensional gas chromatography with time‐of‐flight mass spectrometry for the untargeted metabolic profiling of Daphnia magna in control and salinity‐exposed samples. Examination of the results confirmed the outperformance of comprehensive two‐dimensional gas chromatography with time‐of‐flight mass spectrometry over gas chromatography with mass spectrometry for the detection of metabolites in D . magna samples. The peak areas of multivariate curve resolution–alternating least squares resolved elution profiles in every sample analyzed by comprehensive two‐dimensional gas chromatography with time‐of‐flight mass spectrometry were arranged in a new data matrix that was then modeled by partial least squares discriminant analysis. The control and salt‐exposed daphnids samples were discriminated and the most relevant metabolites were estimated using variable importance in projection and selectivity ratio values. Salinity de‐regulated 18 metabolites from metabolic pathways involved in protein translation, transmembrane cell transport, carbon metabolism, secondary metabolism, glycolysis, and osmoregulation.